Analisis Post Positivisme Hukum Pada Paradigma Guba And Lincoln Melalui Putusan Mk No. 90/PUU-XXI/2023 Terhadap Syarat Usia Capres-Cawapres - Fitri, Rizki Rahayu (Indonesian Journal Publisher, 2024)
This study aims to analyze the legal implications of Constitutional Court Decision No. 90/PUU-XXI/2023 concerning the minimum age requirement for presidential and vice-presidential candidates under Article 169 (q) of the Election Law, viewed as discriminatory against younger candidates with leadership potential. Using a post-positivist approach within the Guba and Lincoln paradigm, this research examines the Court’s role in either upholding or reforming legal norms to align with social dynamics. The method employed is a literature study and qualitative analysis, describing the post-positivist perspective in legal philosophy as a foundation for evaluating the constitutionality of the age requirement. The findings indicate that the Court proposes an alternative criterion—leadership experience as a regional head—as a substitute for the minimum age requirement, considering relevant social changes. The post-positivist approach emphasizes that law is not a static system but a social construct that must adapt to moral and cultural contexts. In conclusion, legal norms must be flexible and capable of re-evaluation in evolving social situations to maintain fairness and relevance in democratic processes. This decision demonstrates that Indonesia’s legal framework needs to accommodate youth participation in government without imposing discriminatory restrictions.